Efficient Electrochemical Reduction of CO2 to Formate in Methanol Solutions by Mn‐Functionalized Electrodes in the Presence of Amines. Issue 37 (25th May 2022) - Stuardi, Francesca Marocco; Tiozzo, Arianna; Rotundo, Laura; Leclaire, Julien; Gobetto, Roberto; Nervi, Carlo
Abstract: Carbon cloth electrode modified by covalently attaching a manganese organometallic catalyst is used as cathode for the electrochemical reduction of CO2 in methanol solutions. Six different industrial amines are employed as co‐catalyst in millimolar concentrations to deliver a series of new reactive system. While such absorbents were so far believed to provide a CO2 reservoir and act as sacrificial proton source, we herein demonstrate that this role can be played by methanol, and that the adduct formed between CO2 and the amine can act as an effector or inhibitor toward the catalyst, thereby enhancing or reducing the production of formate. Pentamethyldiethylentriamine (PMDETA), identified as the best effector in our series, converts CO2 in wet methanolic solution into bisammonium bicarbonate. Computational studies revealed that this adduct is responsible for a barrierless transformation of CO2 to formate by the reduced form of the Mn catalyst covalently bonded to the electrode surface. As a consequence, selectivity can be switched on demand from CO to formate anion, and in the case of (PMDETA ) an impressive TONHCOO− of 2.8×10 4 can be reached. This new valuable knowledge on an integrated capture and utilization system paves the way toward more efficient transformation of CO2 into liquid fuel. Abstract : Carbon cloth electrodes were modified by attaching a manganese organometallic catalyst to the surface by covalent bonds. The system has been used for the electrochemical reduction of CO2 in presence of amines in methanol solution. The enhanced CO2 solubility and the use of pentamethyldiethylentriamine (PMDETA) induce change in chemical selectivity from CO to formate, with very high performances and high selectivity.